The Leveraging 4c Competencies in EFL Classroom - Aeni, Nur; Rasmi Djabba; Tuti Wijayanti; Akhtem A. Dzhelilov; Asriati Asriati (MultiTech Publisher, 2023)
Modifying 4C Competencies in EFL Classrooms Following Pandemic. The adoption of 4C competences in post-pandemic EFL classrooms is the main focus of this study. The researcher employed the descriptive qualitative method. Both observation and interviews were used to get data for this investigation. The lecturer for the class on extensive reading and the second-year English language study program students who were enrolled in it. The Extensive Reading lecturer and students have implemented the 4C skills in the teaching and learning process, according to the data analysis results. Based on the results of the research, the 4C competencies support students' creativity as part of the application of creative competencies. One of the lecturer's assignments in the classroom was to have the students fresh concepts for the content being covered.